Good Work. Issue 1 (10th June 2015) - Clark, Samuel
Abstract: Work is on one side a central arena of self‐making, self‐understanding, and self‐development, and on the other a deep threat to our flourishing. My question is: what kind of work is good for human beings, and what kind bad? I first characterise work as necessary productive activity. My answer to my question then develops a perfectionist account of the human good: (1) the good is the full development and expression of human potentials and capacities; (2) this development and expression happens over a lifetime through appropriate practice. Work is thus a problem of human development, and I address that problem by considering three central human capacities: that we are passionate choosers, skilled makers, and social negotiators. For each, I ask: what does this capacity need from our work if it is to develop towards full and flourishing expression? Answering that question leads to a three‐part account of good work as requiring: (1) a distinctive kind of pleasure, involving both unselfconscious flow and supervisory self‐attention; (2) skill, which I describe via the ideal of craft; and (3) democracy, which I define as a form of life in which each is able to develop and use both expressive and receptive capacities.